The Balkans: A view into the future without internal and regional stability there is no integration into Europe - Kovačević Živorad (Međunarodni Problemi, 2002)
The author analyses the present situation and the prospects of internal and regional stability and security in the countries of the European South East. He says that we have now some peace and some stability and security in the region. The peace is fragile and more the state of no-war than stable peace. The fact remains that the self-sustaining regional stability remains a good distance away. The sources of regional instability are in uneliminated consequences of the recent wars and in the fact that nowhere in the region the complete discontinuity with the policies, ideologies, way of thinking and institutional set-up inherited from previous regimes has been realized. The region needs the coherent approach and active participation of the international community and its military presence in Bosnia, Kosovo and Macedonia for years to come. Let's not delude ourselves: if the troops were withdrawn today who could tell what would happen tomorrow.